Gender Differences in Shirking: Monitoring or Social Preferences? Evidence from a Field Experiment - Per-Olov Johansson; Arizo Karimi; J. Peter Nilsson (Institute for the Study of Labor (IZA), 2014)
This paper studies gender differences in the extent to which social preferences affect workers' shirking decisions. Using exogenous variation in work absence induced by a randomized field experiment that increased treated workers' absence, we find that also non-treated workers increased their absence as a response. Furthermore, we find that male workers react more strongly to decreased monitoring, but no significant gender difference in the extent to which workers are influenced by peers. However, our results suggest significant heterogeneity in the degree of influence that male and female workers exert on each other: conditional on the potential exposure to same-sex co-workers, men are only affected by their male peers, and women are only affected by their female peers.
Keywords: C23; C93; J24; 330; peer effects; employer-employee data; social preferences; randomized field experiment